Arterial Stiffness Assessment in Healthy Participants Using Shear Wave Elastography - Alyami, Jaber; Almutairi, Fahad (Current Medical Imaging, 2022)
Background: Arterial stiffness is an important biomarker for cardiovascular disease. Shear wave elastography (SWE) provides quantitative estimates of tissue stiffness. Objective: This study aimed to provide reference values for arterial wall, assessing the suitability of SWE to quantify elasticity of the common carotid artery (CCA) and evaluating inter-and intra-observer reproducibility. Methods: A Supersonic Aixplorer ultrasound system with L15-4 probe was used to scan longitudinal sections of the CCA. Young’s modulus (YM) was measured within 2-mm regions of interest. Reproducibility was assessed within a subgroup of 16 participants by two operators (one novice and one experienced) during two sessions >one week apart. Results: This study involves seventy-three participants with a mean age of 40±10 years and a body mass index of 26 ±6 kg/m2. YM estimates were 59 kPa ±19 in men and 56 kPa ±12 in women. The average YM of the CCA walls was 58 kPa ±15 (57 ±15 kPa for the anterior wall and 58 ±20 kPa for the posterior wall, p=0.75). There was no significant difference in the mean of YM estimates of the CCA between the observers (observer: one 51 ±14 kPa and observer two: 55 ±17 kPa[p=0.46]). Interand intra-observer reproducibility was fair to good (Intra-class correlations, ranging from 0.46 to 0.71). Inter-frame variability was 28%. Conclusion: In healthy individuals, SWE provided an estimate of YM of the CCA (58 kPa) with fair to good reproducibility. This study demonstrated the potential of using SWE for assessing biomechanical properties of blood vessels.
Keywords: dissection